1981
DOI: 10.1128/jvi.37.1.92-102.1981
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of multiple forms of simian virus 40 large T antigen

Abstract: Subclasses of simian virus 40 large T antigen in simian virus 40-transformed and -infected cells separated by zone velocity sedimentation in sucrose density gradients have been characterized. Three forms of large T antigen were distinguished: a 5 to 6S form, a 14 to 16S form, and a 23 to 25S form. These forms appeared to differ biochemically and biologically. Differential labeling experiments suggested that the 5 to 6S form was less highly phosphorylated than the faster-sedimenting forms. The 23 to 25S form wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
86
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(97 citation statements)
references
References 40 publications
(47 reference statements)
11
86
0
Order By: Relevance
“…(We have not yet analyzed this peptide, because it represented a minor species.) Other investigators reported a positive correlation between the degree of phosphorylation of large T and its affinity for DNA (16,31); in addition, the DNA-binding capacity of large T was found to be restricted to its oligomeric forms (4), which are phosphorylated to a higher degree than monomers (10,16). On the other hand, Shaw and Tegtmeyer found no difference in the specific DNA-binding potential between phosphorylated and dephosphorylated large T (41).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…(We have not yet analyzed this peptide, because it represented a minor species.) Other investigators reported a positive correlation between the degree of phosphorylation of large T and its affinity for DNA (16,31); in addition, the DNA-binding capacity of large T was found to be restricted to its oligomeric forms (4), which are phosphorylated to a higher degree than monomers (10,16). On the other hand, Shaw and Tegtmeyer found no difference in the specific DNA-binding potential between phosphorylated and dephosphorylated large T (41).…”
Section: Discussionmentioning
confidence: 94%
“…Peptides containing identical phosphate acceptors but differing in their phosphorylation extent must derive from different molecular classes of large T. Several investigators described subspecies of large T differing in their aggregation state (4,10,16) or their DNA-binding capacity (16, 32) on one side, or their degree of phosphorylation on the other (15,31). It will be interesting to investigate how different aggregation forms or DNA-binding species of large T correlate with the phosphorylation state of specific sites.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interactions of Nef with cellular factors are likely to be the key to the still enigmatic mechanisms of Nef function(s). We therefore tried to characterize these interactions in a general way by zone velocity sedimentation, an approach that has been successfully used to study interactions of simian virus 40 (SV40) T antigen [28,291. We report here an interaction of Nef with cellular components identifying actin as a major binding partner.…”
mentioning
confidence: 99%
“…In vitro, large T binds to DNA, specifically to the origin of replication on the viral genome (20,48,54,58), and has ATPase activity, which may be an intrinsic property of the molecule (60). It exists in monomeric, dimeric, and tetrameric forms (4,11,39) and associates with a cellular 53,000-dalton (53K) protein (11,18). It is not understood how large T performs several distinct functions.…”
mentioning
confidence: 99%